A flexible organic inverter made from printable materials for synergistic ammonia sensing. Issue 26 (19th June 2017) - Besar, Kalpana; Dailey, Jennifer; Zhao, Xingang; Katz, Howard E.
Abstract : An inverter circuit made from solution deposited dielectrics and semiconductors gives a clear voltage output signal in response to ppm levels of ammonia. Abstract : Ammonia is a nearly ubiquitous environmental pollutant, and occupational or random exposure to sufficiently high levels is known to result in a variety of lung ailments. In this work, we present a flexible architecture for an ammonia inverter sensor consisting of a conductive plastic substrate, a bi-layer polymer dielectric, and patterned gold electrodes. n- and p-Type semiconductors (2, 2′-[(2, 5-dihexadecyl-3, 6-dioxo-2, 3, 5, 6-tetrahydropyrrolo[3, 4- c ]pyrrole-1, 4-diylidene)dithiene-5, 2-diyli-dene]dimalononitrile (DPPCN) and poly(3-hexylthiophene-2, 5-diyl) (P3HT), respectively) were deposited on the inverter in specific quantities in order to ensure complementary, reverse responses in the presence of ammonia gas. Our sensor shows a sensitivity down to 0.5 ppm ammonia, and has good stability in the presence of other vapors. The sturdy structure and easily understood transduction mechanism of this sensor make it potentially very useful for point-of-care sensing.